Effects of compression tights on calf muscle oxygenation and venous pooling during quiet resting in supine and standing positions - Bringard, A.; Denis, R.; Belluye, N.; Perrey, S. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: We applied near-infrared spectroscopy (NIRS) to evaluate in resting conditions the effects of compression tights (CT) on calf muscle oxygenation and venous pooling compared with Lycra® elastic tights (ET) and shorts (no compression) according to the body posture (supine vs standing). Methods: Twelve sportsmen regularly involved in endurance training volunteered to this study. Their average age, height and weight (±SD) were 26.5±2.6 years, 177±6 cm and 70.1±4 kg, respectively. Tissue oxygenation index (TOI), deoxyhemoglobin (HHb), and blood pooling (Hbtot) of the right gastrocnemius medialis were continuously monitored at 2 Hz using a NIRS device (NIRO-300, Hamamatsu Photonics, Japan). A home made transducer was used to measure applied pressure at the interface between skin and clothing over the calf area. Subjects were asked to realize a supine-standing protocol (5 min for each position) by wearing CT, ET or shorts in a counterbalanced order on the same day. Results: HHb and Hbtot concentration changes were significantly lower whereas TOI was significantly higher by wearing CT compared with shorts and ET (P<0.001) as did supine compared to upright postures. The mean pressures applied over the calf were 5.6 and 23.2 mmHg during supine and 5 and 24.1 mmHg during standing for ET and CT, respectively. Pressures were significantly different among clothing according to the following rank order: CT>ET>shorts (P<0.001). Conclusions: CT compared to ET have positive effects on calf muscle oxygenation and venous pooling in quiet resting positions.